Immune mechanisms in C57B1 mice genetically resistant to Trypanosoma congolense infection. I. Effects of immune modulation - Whitelaw, D.D.; Macaskill, J.A.; Murray, M. (Wiley, 1983)
Summary The effect of immune modulation on the pattern and course of infection with T. congolense was investigated in a strain of mice (C57B1) which is known to possess a significant degree of trypanotolerance, and a susceptible strain (CFLP) which rapidly succumbs to infection. Immunosuppression of C57B1 mice by splenectomy, cyclophosphamide treatment or gamma irradiation reduced their survival to near that of susceptible strains of mice. In contrast, attempts to enhance the immune response of susceptible CFLP mice using either a variety of immunostimulants, simultaneous vaccination with irradiated parasites at the time of infection, passive immunization or reducing the number of parasites used for infection, failed to confer a level of protection comparable to that of C57B1 mice. It was concluded that the basis of trypanotolerance, although immunological in nature, is associated with, as yet, undetermined factors.